Aplikasi Penolong Usaha Mikro, Kecil, dan Menengah untuk Penjualan Melalui e-Commerce - Alvi Rahmadhani; Arya Septiawan; Brian Adam Bhagaskara; Arwin Datumaya Wahyudi Sumari (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2023)
The fast development of information technology has triggered tight business competition that also impacts the development of Micro, Medium, and Small Enterprises (MSME). Unfortunately, the MSME owners need to be made aware of the importance of the application of information technology, especially e-Commerce, to leverage product sales, as it causes their products to be less known by the public and affects their sales. This study aims to develop an MSME product sale helper besides familiarizing the MSME owners with Information Technology (IT) to carry out the direct sale. The phases of this research cover the data collection, analysis, application program design and implementation, and application testing using the blackbox method. The result of the study is a website-based e-Commerce application to help MSMEs market their products digitally.